2009
DOI: 10.1021/nn901107p
|View full text |Cite
|
Sign up to set email alerts
|

Probing Compositional Variation within Hybrid Nanostructures

Abstract: Ќ These authors contributed equally to this work. P latinum-based bimetallic alloys are highly desirable for their potential in magnetic storage, sensing, and catalysis, 1Ϫ5 often displaying properties that are independent of their constituent materials. 6 In addition to changes in the geometric distribution of the individual atoms, the unique structure and bonding in bimetallics can also lead to alterations in the electronic structure of the material. For example, PtNi alloys show enhanced activity for oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…Such hybrid nanoheterostructures, with the ferromagnetic component grown directly onto the semiconductor, could be also useful for studying nanoscale spin injection into semiconductor nanostructures. 27,28 ■ CONCLUSION In summary, monodisperse CZTS nanocrystals were synthesized via a hot-injection method and further used as support to produce CZTS−PtCo and CZTS−PtNi nanoheterostructures. CZTS-PtCo materials showed much higher photocatalytic hydrogen generation activity than CZTS and even CZTS-Pt nanoparticles.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Such hybrid nanoheterostructures, with the ferromagnetic component grown directly onto the semiconductor, could be also useful for studying nanoscale spin injection into semiconductor nanostructures. 27,28 ■ CONCLUSION In summary, monodisperse CZTS nanocrystals were synthesized via a hot-injection method and further used as support to produce CZTS−PtCo and CZTS−PtNi nanoheterostructures. CZTS-PtCo materials showed much higher photocatalytic hydrogen generation activity than CZTS and even CZTS-Pt nanoparticles.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For example, at the high temperatures at which colloidal synthesis is typically carried out, the overgrown material may adapt to the lattice parameters of the seed at the interface (coherency strain) (Dunstan, 1997;Chen et al, 2003;Xu et al, 2015). In other circumstances, the constituent atomic species of the connected materials may interdiffuse, accommodating variation in the chemical composition and/or crystal-lattice parameters across the heterojunction regions (Koo and Korgel, 2008;Yuhas et al, 2009). In the extreme cases of exceedingly large misfit, plastic relaxation may induce formation of interfacial defects, such as dislocations and stacking faults (Dunstan, 1997;Markov, 2003;Carbone and Cozzoli, 2010;Li et al, 2014).…”
Section: Facet-controlled Regioselective Heterogeneous Nucleation Andmentioning
confidence: 99%
“…In the extreme cases of exceedingly large misfit, plastic relaxation may induce formation of interfacial defects, such as dislocations and stacking faults (Dunstan, 1997;Markov, 2003;Carbone and Cozzoli, 2010;Li et al, 2014). Experimental results (Casavola et al, , 2009Koo and Korgel, 2008;Deka et al, 2009;Yuhas et al, 2009;Liakakos et al, 2014) and thermodynamic modeling (Sadowski and Ramprasad, 2010;Xu et al, 2015) have indicated that the temperature and the particular chemical pathways underlying MHNC formation are decisive in determining whether either uniformly alloyed, graded, or abrupt interfaces may be attained.…”
Section: Facet-controlled Regioselective Heterogeneous Nucleation Andmentioning
confidence: 99%
See 1 more Smart Citation
“…XAS is used to detect small differences in the structure of colloidal nanocrystals 209 which can be difficult to discern using EM and XRD. 206 Nevertheless, structural evaluation of bimetallic NPs (Ru-Pt NPs) 207 is clarified by using EXAFS, XANES and XRD. 7 Moreover, it is possible to monitor different reaction steps 137 by checking both the NPs surface passivation and the different oxidation states of CdSe quantum dots.…”
mentioning
confidence: 99%